DELEGASI REGULASI DAN SIMPLIFIKASI REGULASI DALAM PEMBENTUKAN PERATURAN KEPALA DAERAH - Suherman, Petrus Kadek (Fakultas Hukum Universitas Mahasaraswati Denpasar, 2017)
In local governance should be based on regulations, to be able to provide services and the protection of fundamental rights of the people. On the other hand the rules or regulations of one of them made by local governments in both the types of regulations or regulations of the regional chief. The authority of local government and regional chiefs to make local laws and regulations based on the regional heads attribution and delegation authority. In practice, this often results in the occurrence of obesity regulation or regulation created a high quantity. The terms of substance the principle of the legislation formation was good enough delegated substantive content regulated in the area.